Ziarah Prihatin UMP appreciates outstanding SPM student obtained 9 A - Mimi Rabita, Abdul Wahit (2023)
KUANTAN, 11 June 2023 - Losing a mother while sitting the Sijil Pelajaran Malaysia (SPM) examination did not deter Mohamad Abdul Jani Hayi, a student of Sekolah Menengah Sains Sultan Haji Ahmad Shah (SEMSAS) Kuantan to obtain 9 A.